Microbes in Tumoral In Situ Tissues and in Tumorigenesis - Feng, Xue; Han, Lu; Ma, Sijia; Zhao, Lanbo; Wang, Lei; Zhang, Kailu; Yin, Panyue; Guo, Lin; Jing, Wei; Li, Qiling (Frontiers in Cellular and Infection Microbiology, 2020)
Cancerous tumors are severe diseases affecting human health that have a complicated etiology and pathogenesis. Microbes have been considered to be related to the development and progression of numerous tumors through various pathogenic mechanisms in recent studies. Bacteria, which have so far remained the most studied microbes worldwide, have four major possible special pathogenic mechanisms (modulation of inflammation, immunity, genetics, and metabolism) that are related to carcinogenesis. This review aims to macroscopically summarize and verify the relationships between microbes and tumoral in situ tissues from cancers of four major different systems (urinary, respiratory, digestive and reproductive); the abovementioned four microbial pathogenic mechanisms, as well as some synergistic pathogenic mechanisms, are also discussed. Once the etiologic role of microbes and their precise pathogenic mechanisms in carcinogenesis are known, the early prevention, diagnosis, and treatment of cancers would progress significantly.